PENGEMBANGAN PENGEMBANGAN MODEL PERBAIKAN DAN PENINGKATAN KEKUATAN STRUKTUR SAMBUNGAN BALOK-KOLOM PADA BANGUNAN PASCA GEMPA - sri murni Dewi; Wisnumurti; Ari Wibowo; Adi Susetyo Dermawan (Rekayasa Sipil, 2023)
This paper presents an experimental study on repairing damaged beam-column reinforced concrete joints using carbon fiber reinforced polymer (CFRP). The test objects were in the shape of the letter T which represented the beam-column connection. The test object came from the previous research which had been failure. The retrofitted action includes strengthening the column position, injection with concrete glue and adding CFRP. Two kinds of CFRP were use, CFRP sheets (EB) and CFRP strips (NSM). The integrity of concrete after injection were tested with Ultrasonic Pulse Velocity (UPV). The retrofitted specimens were tested in loading frame to occurred strength, stiffness and ductility for each kind of retrofitted action. Three kind of tested were held, bending in one direction, shearing in one direction, and quasi cyclic bending. The selection test adjusted to the damage history of specimen.